The level of leadership skills among gifted students in the general education stage in the Qassim region - Aljuhany, Noorah Yousef (Journal of Educational and Psychological Sciences, 2023)
The study aimed to know the level of leadership skills of gifted students in public education in the Qassim region during the Corona crisis (COVID-19). The researcher used the descriptive survey method, and to collect data, the leadership skills scale was used, prepared by Louis Roetz, translated by Zureikat (2018). The sample consisted of (176) talented male and female students in the general education stage in the Qassim region. The results showed that the level of leadership skills of gifted students in public education in the Qassim region during the Corona crisis came with a total average (4.16 out of 5) and a verbal rating (large), and the arithmetic averages of the scale expressions ranged between (4.61-3.31), i.e. between (very large, large and medium). And the presence of statistically significant differences due to the variable of sex in favor of females, and the presence of statistically significant differences for the variable of the school stage in favor of the primary stage. Based on the results, the researcher recommended implementing training courses to educate teachers and parents about the level of leadership skills of gifted students, and how to deal with them, in proportion to the characteristics of each stage. Especially in times of crisis. The researcher also suggests conducting more research on: The leadership skills of gifted students and their relationship to some variables: such as students’ attitudes towards school, social intelligence and others.